2018
DOI: 10.1177/1073191118781014
|View full text |Cite
|
Sign up to set email alerts
|

SCORS-G and Card Pull Effect of TAT Stories: A Study With a Nonclinical Sample of Children

Abstract: Previous research has shown that stimulus pull is one of the contributory factors influencing Thematic Apperception Test (TAT) responses. In recent years, there has been a resurgence of studies examining this. In particular, the Social Cognition and Object Relations Scale-Global Rating Method (SCORS-G) has been employed to examine stimulus pull in adult clinical and nonclinical samples. The present study is the first attempt to examine this issue in a nonclinical sample of children. Ninety-eight children from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
5
19
0
Order By: Relevance
“…Siefert et al (2016) found that the interaction between person by card effects accounted for the greatest proportion of variance for affective‐relational dimensions whereas cognitive dimensions were more influenced by person factors. Auletta et al (2018) extended work in this area by replicating findings in a nonclinical sample of children (between ages 7 and 13). Their card set included four TAT cards (Cards 1, 2, 3BM and 4) that had been used in earlier card pull studies (Siefert et al, 2016; Stein et al, 2014), as well as two cards that had not previously been examined (Cards 8BM and 16).…”
Section: The Scors‐g and Card Pull On The Tatmentioning
confidence: 90%
See 1 more Smart Citation
“…Siefert et al (2016) found that the interaction between person by card effects accounted for the greatest proportion of variance for affective‐relational dimensions whereas cognitive dimensions were more influenced by person factors. Auletta et al (2018) extended work in this area by replicating findings in a nonclinical sample of children (between ages 7 and 13). Their card set included four TAT cards (Cards 1, 2, 3BM and 4) that had been used in earlier card pull studies (Siefert et al, 2016; Stein et al, 2014), as well as two cards that had not previously been examined (Cards 8BM and 16).…”
Section: The Scors‐g and Card Pull On The Tatmentioning
confidence: 90%
“…To date, three studies have evaluated TAT card pull effects using the SCORS‐G system. These studies have shown that person factors (e.g., the psychological characteristics of the individual), card factors (e.g., features of the stimulus) and the interaction between the two contribute to variance in SCORS‐G ratings in both adults and children (Auletta et al, 2018; Siefert et al, 2016; Stein et al, 2014). Findings have suggested that variance in scales assessing cognitive dimensions of relational schemas are best explained by person factors whereas variance in affective‐relational elements is better explained by card by person interactions.…”
Section: The Tat and The Scors‐gmentioning
confidence: 99%
“…One can then show [22,23,[26][27][28]] that for T → ∞ the system remains in the state |n , while the apparatus pointer shifts by an amount proportional to n|Ô|n , thus providing partial information about |n . However, in the realistic case of finite T and a corresponding non-infinitesimal average interaction strength, the system becomes entangled with the apparatus, disturbing the initial state [29,[35][36][37].…”
Section: Protective Measurementmentioning
confidence: 99%
“…[26], which estimated the effect of the turn-on and turnoff of the measurement interaction on the adiabaticity of the interaction. Recently, the case of finite measurement times in a protective measurement and its influence on the reliability of the measurement were studied [29,35], and a framework for the perturbative treatment of time-dependent measurement interactions in a protective measurement has been developed and applied to specific examples [36,37]. None of these existing studies, however, have shown how to systematically minimize the state disturbance in a protective measurement for the physically and experimentally relevant case of finite measurement times and interaction strengths, such that the reliability of the protective measurement can be maximized.…”
Section: Introductionmentioning
confidence: 99%
“…If the system starts out in an eigenstate of its Hamiltonian, then this state remains approximately unchanged during the measurement while the apparatus pointer is shifted by an amount proportional to the expectation value of in the initial state [11]. Applications of protective measurements include the direct measurement of the quantum state of a single system [4][5][6][7][12][13][14][15][16], studies of particle trajectories [17,18], determination of stationary states [14], translation of ergodicity into the quantum realm [15], fundamental investigations of quantum measurement [2, 4-6, 12, 19, 20], and the description of two-state thermal ensembles [15]. An experimental realization of a protective measurement using photons has been reported in Ref.…”
Section: Introductionmentioning
confidence: 99%